PENGARUH PERENCANAAN PAJAK, KEBIJAKAN HUTANG, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN: NILAI PERUSAHAAN - Hikmat Fajar (Yayasan Kayyis Mulia Jaya, 2025)
This research aims to provide empirical evidence of the influence of Tax Planning, Debt Policy and Dividend Policy on Company Value. This research uses a quantitative approach and the data used is secondary data. The population in this research is Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The method for determining the sample uses purposive sampling. A sample of 13 companies was obtained over a 5 year period so that the total obtained was 65 sample data. When carrying out the test there were extreme values so that 25 sample data experienced outliers. Data processing using the eviews version 12 program, by carrying out Descriptive Statistics Tests, Panel Data Regression Model Analysis, Model Selection Tests (Chow Test, Hausman Test and Lagrange Multiplier Test) with the selected model being the Random Effect Model, Classical Assumption Test (Normality Test , Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test), Panel Data Regression Analysis, Hypothesis Test (Coefficient of Determination Test, Partial t Test and Test Simultaneous F). The t test results show that partial Tax Planning does not have a significant effect on the Company Value decision. Debt Policy partially has a significant effect on Company Value. Dividend Policy partially has no significant effect on Company Value. The results of the F test show that simultaneously Tax Planning, Debt Policy and Dividend Policy have a significant effect on Company Value. Keywords: The Influence Of The Tax Planning, Debt To Policy, and Dividend Policy On Company Value